2020
DOI: 10.1213/ane.0000000000004639
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Infectious Complications After Intrathecal Drug Delivery System Implant for Cancer-Related Pain Is Low Despite Frequent Concurrent Anticancer Treatment or Leukopenia

Abstract: BACKGROUND: The efficacy of intrathecal drug delivery (IDD) for cancer-related pain is well established. Cancer therapies are often associated with immunosuppression and increased risk of infection, and the rate of infection after intrathecal drug delivery system (IDDS) implant in cancer patients has been reported as 2.4%–6.3%. Our objective is to report on the rate of surgical site infections (SSI) in patients implanted with IDDS for cancer-related pain and to provide a data-driven discussion on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This included cases where the pump was located within the radiation field and subjected to relatively high RT doses, in some instances more than the manufacturer's suggested maximum limit (7). The absence of infectious complications is notable as IDDS surgical site infections for cancer patients has been reported as 2.4-6.3% (10-12) at outside institutions and 0.9% in our own practice (13). Cancer types and locations were well represented, and RT spanned wide dose and intensity ranges.…”
Section: Discussionmentioning
confidence: 70%
“…This included cases where the pump was located within the radiation field and subjected to relatively high RT doses, in some instances more than the manufacturer's suggested maximum limit (7). The absence of infectious complications is notable as IDDS surgical site infections for cancer patients has been reported as 2.4-6.3% (10-12) at outside institutions and 0.9% in our own practice (13). Cancer types and locations were well represented, and RT spanned wide dose and intensity ranges.…”
Section: Discussionmentioning
confidence: 70%
“… 102 , 116 , 122 , 124 , 125 A recent retrospective review in a large cancer center showed an infection incidence of 0.9% despite frequent concurrent cancer treatment and leukopenia. 127 In other studies, the incidence of infection in the cancer patient population was 2.7–3.2%. 128 , 129…”
Section: Data Evaluation and Discussionmentioning
confidence: 88%
“…Studies have shown contrary to this belief, the rates of surgical site infection for pain implants are not greater in cancer patients compared to patients without cancer. 19 , 22 However, a study by Hoelzer et al evaluating spinal cord stimulator implants did have a statistically significant decrease in incidence of surgical site infection with use of post-operative antibiotics for 7 days in non-cancer patients. 23 This practice may reflect provider preference based on these findings.…”
Section: Discussionmentioning
confidence: 99%